ANALISIS KEMAMPUAN PEMECAHAN MASALAH SISWA MATERI LOGIKA MATEMATIKA - Imam Saifuddin (Prodi Pendidikan Matematika Universitas PGRI Ronggolawe, 2019)
This study aims to determine the problem solving abilities students of mathematical logic. The approach used is a qualitative approach and descriptive statistics, namely with qualitative data used in the form of observations of the steps of problem posing and students problem solving abilities when learning takes place. Data in the form of test results of student work and data collection conducted interviews with 3 subjects representing various levels, namely students with low, medium and high abilities. The results showed that: a) students did not understand the problem such as not linking information obtained; b) students are less able to arrange steps to plan settlement well; c) students do not carry out plans on all questions; d) students cannot make conclusions.